Fourth Year Honourable Mention: The Young Classic: WRIT 4700, Advanced Topics in Periodical Writing. CD: Paul McLaughlin. - Favrin, Mia (Jan Rehner Prize for Writing, 2017)
Mia Favin’s feature article, “The Young Classic” introduces us to Jordan Gauthier, a 23-year old drum technician based out of Ottawa, Ontario. Gauthier founded the “Young Classic” Drum Company, and builds the drums kits for some of Canada’s biggest bands—including 2017 Juno award winners the Strumbellas, July Talk and The Dirty Nil—as well as a product endorser, and sought-after techie for big shows like Gord Downie’s solo act and the 2017 Junos. Favrin’s presents a fascinating biography of the eclectic and accomplished Gauthier, cogently describing how he’s made his own way to the top of his profession, and using smooth, interesting prose to keep our attention throughout. She’s also clearly well aware of genre conventions, since the style and tone of her feature article is pitch perfect.